Faktor yang Berpengaruh pada Nilai Perusahaan (Emite sektor Farmasi di BEI Tahun 2019-2021) (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This study aims to analyze and obtain empirical evidence regarding the influence of slack resources, leverage, company size and corporate social responsibility disclosure. The population of this study is 12 pharmaceutical sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. Based on the criteria, 10 pharmaceutical sector companies that have been obtained to be used as research samples. This study used the SPSS version 26 analysis test. The data analysis techniques used are classical assumption tests, multiple linear regression tests, and hypothesis tests. The results showed that, partially, leverage affects the value of the company, while slack resources, leverage, company size and disclosure of corporate social responsibility do not affect the value of the company.